Performance Assessment of Thermoelectric Generators with Application on Aerodynamic Heat Recovery - Xiaodong Jia (MDPI AG, 2021)
Based on thermoelectric generators (TEGs), an aerodynamic heat energy recovery system for vehicle is proposed. A mathematical model describing the energy conversion law of the system is established, and the integrated calculation method which combined aerodynamic heating and thermoelectric (TE) conversion is given. Furthermore, the influences of the typical flight Mach number, flight altitudes and the length of TE legs on the energy conversion behavior of energy recovery systems are investigated. The performance of the energy recovery system is analyzed and evaluated. The results show that, the decrease of flight altitude and the increase of Mach number will obviously improve the performance of the heat energy recovery system with TEGs. The increase of leg length will increase the temperature of the hot end of TEGs and reduce the heat absorbed at the hot end. When the external load, Mach number and flight altitude is fixed, there exists an optimal length of legs corresponding to the maximum output power and maximum conversion efficiency of the system. The results will have significant positive impact on thermal protection and management of supersonic/hypersonic vehicles.